Study of PAH formation in laminar premixed toluene and C8H10 aromatics flames. (1st September 2020) - Li, Youping; Zhang, Yiran; Zhan, Reggie; Huang, Zhen; Lin, He
Abstract: Toluene and C8 H10 aromatic fuels are widely proposed as components of surrogate mixtures and usually employed as the prototypical fuels to investigate the combustion properties of aromatic fuels. In this study, the PAH formation of pure C8 H10 aromatics (xylenes and ethylbenzene) and toluene was studied in a laminar premixed flame at atmospheric pressure using laser-induced fluorescence (LIF) diagnostic. The experimental results indicated the aromatic structure has a significant influence on the PAH tendency, and the observed LIF intensities were sequenced by toluene < xylenes < ethylbenzene. A detailed kinetic model was employed to validate against the experimental results based on the ROP analysis. The predicted mole fraction profiles of PAHs were consistent with the measured PAH tendency for toluene, o-xylene, and ethylbenzene. The chemical kinetic analysis indicated that benzyl is the most dominant intermediate product in toluene decomposition and precursor in PAH formation, corresponding to methylbenzyl in o-xylene flame, styrene and benzyl in ethylbenzene flame. In the comparison of o-xylene and toluene, the increased methylated groups on the benzenoid ring make the yield of benzylic radicals (mostly methylbenzyl) enhanced, increasing the probability of radical–radical recombination on PAH formation. In the ethylbenzene flame, two secondary CH bonds in the ethyl site are much easier to be abstracted than primary CH bonds in methyl sites of o-xylene. The different bond dissociation energies (BDEs) depended on the aromatic structure can change the distribution of the intermediate species in fuel decomposition, which can result in either an increase or decrease of PAH formation. Additionally, the weak benzylic CC bond makes the initiation of ethylbenzene decomposition easier, which could also explain the fated PAH formation in contrast with toluene and o-xylene. The experimental and kinetic analysis for C8 H10 aromatics and toluene conducted in the present study contributed a deep insight into the PAH formation of aromatics fuels.